PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Leadership is one of the factors that shape and help others to enthusiastically work and achieve the planned object in relation to the success of the organization realize the objectives are largely determined by the high performance leadership and employed in carrying out their duties.